2022
DOI: 10.1002/dta.3379
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive UHPLC–MS/MS method for the analysis of endogenous and exogenous steroids in serum for anti‐doping purposes

Abstract: In the context of steroid analyses, the use of blood could represent a valuable complement to urine. While the blood steroid profile is currently being established to aid unveiling testosterone (T) doping, this matrix is also well suited for detection of exogenous anabolic steroids and steroid esters. In this study, a method to determine a simplified blood steroid profile in combination with the direct detection of exogenous anabolic steroids and steroid esters using just one serum aliquot was developed to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…An instance of SLE with DCM extraction solvent recovered 18 free endogenous and exogenous AASs at recovery efficiencies ranging from 42% (methasterone) to 91% (boldenone) from serum when analyzed using an UHPLC-MS/MS (Langer et al, 2022).…”
Section: Sample Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An instance of SLE with DCM extraction solvent recovered 18 free endogenous and exogenous AASs at recovery efficiencies ranging from 42% (methasterone) to 91% (boldenone) from serum when analyzed using an UHPLC-MS/MS (Langer et al, 2022).…”
Section: Sample Extraction Methodsmentioning
confidence: 99%
“…Sixteen estered AASs observed no significant matrix effects and recovery efficiencies of ≥33% from serum when analyzed via UHPLC-MS/MS, with longer chained esters demonstrating reduced recoverability when extracted via ISOLUTE ® SLE+ with DCM. It was suggested heptane be used to improve AAS ester extraction, but to the detriment of free AAS extraction (Langer et al, 2022).…”
Section: Estered Aas Detectionmentioning
confidence: 99%
“…For instance, Langer et al reported on a strategy on how to combine the quantitation of the endogenous steroids T, Adione, and dihydrotestosterone (DHT) with 18 xenobiotic steroids plus 11 intact testosterone esters as well as 5 further AAS esters 45. A volume of 200 μL of serum was prepared by supported liquid extraction (SLE), concentrated, and analyzed by LC-ESI-QqQ MS for the aforementioned serum steroid ABP markers and the non-esterified target analytes.…”
mentioning
confidence: 99%
“…These methods facilitated serum steroid profiling 10 and proved applicable also to DBS, 11 where considerable advantages especially regarding steroid ester stabilities were documented. 12 Detecting the manipulation of erythropoiesis with newly approved drugs such as luspatercept has been the subject of in-depth investigations, and two analytical approaches utilizing either an automated capillary immunoassay 13 or gel-based electrophoretic methods 14 were shown to be fit-for-purpose and compatible with serum, DBS, and urine analyses.…”
mentioning
confidence: 99%
“…In contrast to urinary steroid (metabolite) analyses, serum and DBS applications employed exclusively liquid chromatographic‐mass spectrometric methods (LC–MS), targeting testosterone, androst‐4‐ene‐3,17‐dione, 5α‐dihydrotestosterone, various testosterone esters, and/or synthetic AAS with and without prior derivatization. These methods facilitated serum steroid profiling 10 and proved applicable also to DBS, 11 where considerable advantages especially regarding steroid ester stabilities were documented 12 …”
mentioning
confidence: 99%